KEMITRAAN PETANI JAGUNG DENGAN PT AVAN PASURUAN DI KELOMPOK TANI MARGO UTOMO I DESA TOYOMARTO KECAMATAN SINGOSARI - Anul, Vornia (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2023)
This study aims to determine the partnership between Corn Farmers and PT Avan Pasuruan in Singosari District. The partnership pattern in this study is the Agribusiness Operational Cooperation (KOA) partnership pattern, in which the partner group provides land, facilities, and labor, while the partner companies provide capital and corn seeds. The partnership as a facilitator between the Margo Utomo I farmer groups, farmers get cheap fertilizer and corn seeds with an average value of 73%. Partnership as a motivator, namely PT Avan Pasuruan encourages farmers to always work together among group members with an average value of 87%. Kemitraan as a communicator, namely PT Avan Pasuruan conveys information through electronic media and always conveys the latest information about corn plants with an average value of 89%. And finally, as the role of farmer groups and farmers, there is a division of tasks between members to achieve group goals in partnership with an average value of 88%. Data analysis in this study uses descriptive qualitative. This study uses validity and reliability tests. In the validity test, this study has a correlation coefficient that is greater than r table 0.449 (r table value for n = 32) so that all indicators of the research variables are valid. The reliability test has a Cronbach alpha coefficient which is quite large from 0.60 so that it can be said that all measurements of each variable from the questionnaire are reliable, which means that the questionnaire used in this study is a reliable questionnaire. Keywords: Partnership; Corn; Singosari